Strategi Kontraterorisme Iran terhadap ISIS-K: : Antara Kepentingan Keamanan dan Ambisi Geopolitik - Hawhyanus Jiwana (Journal of Peace, Security and Democracy, 2025)
The Islamic State of Iraq and Syria – Khorasan Province (ISIS-K) has emerged as a transnational threat in Southwest Asia, posing a significant challenge to Iran’s national security. This article analyzes Iran’s counterterrorism strategy in responding to the presence and operations of ISIS-K in the Khorasan region. Employing a qualitative approach and literature-based analysis, this study draws from policy documents, academic literature, and official statements. The findings reveal that Iran adopts an active defense posture involving intelligence coordination, border security enhancement, and regional cooperation, particularly with Afghanistan and Russia. These strategies are driven not only by domestic security concerns but also by Iran’s geopolitical interest in maintaining regional influence. The study concludes that Iran’s response to ISIS-K reflects an effort to safeguard internal stability while shaping a regional security order aligned with its strategic interests.